Vietnam : a history of the war - Freedman, Russell, 1929-2018 (Holiday House, 2019)
Offers a concise account of the Vietnam War, describing how America, a superpower caught up in Cold War politics, became involved in the war; battles and events in Vietnam; the experiences of American soldiers sent into the jungles to fight; and ultimately the legacy of the Vietnam War. Features black-and-white photographs, a timeline, and a glossary of terms.